2021
DOI: 10.3390/pathogens10050558
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances on Tilapia Streptococcosis

Abstract: Streptococcus agalactiae, often referred to as group B streptococci (GBS), is a severe pathogen that can infect humans as well as other animals, including tilapia, which is extremely popular in commercial aquaculture. This pathogen causes enormous pecuniary loss, and typical symptoms of streptococcosis—the disease caused by S. agalactiae—include abnormal behavior, exophthalmos, and meningitis, among others. Multiple studies have examined virulence factors associated with S. agalactiae infection, and vaccines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 93 publications
0
29
0
Order By: Relevance
“…Several of the bacterial genera we found to be differentially abundant in fish skin contained species pathogenic to tilapia, including Aeromonas (hydrophila) (Dong et al, 2017), Streptococcus (agalactiae) (Zhang, 2021) and Pseudomonas (fluorescens) (Hal and El-Barbary, 2020). In addition to these fish skin enriched genera, further potentially pathogenic taxa were detected in pond water and fish skin.…”
Section: Clr Abundancementioning
confidence: 85%
“…Several of the bacterial genera we found to be differentially abundant in fish skin contained species pathogenic to tilapia, including Aeromonas (hydrophila) (Dong et al, 2017), Streptococcus (agalactiae) (Zhang, 2021) and Pseudomonas (fluorescens) (Hal and El-Barbary, 2020). In addition to these fish skin enriched genera, further potentially pathogenic taxa were detected in pond water and fish skin.…”
Section: Clr Abundancementioning
confidence: 85%
“…Other studies showed RPS (relative percentage survival) value after tilapia vaccination consisting of GBS FsbA protein reached 40.63% [67]. It allows to define FsbA as a multifunctional immunogenic protein, including immunoprotection as well as activation of the innate immune responses in the host and relevant antibody responses [68].…”
Section: Fsba Proteinmentioning
confidence: 98%
“…However, recently, the development of oral feed-based vaccines has been focused upon for them to become an ideal approach for preventing and controlling fish infectious diseases. Up to now, oral vaccines based on live attenuated S. agalactiae , E. coli , Bacillus subtilis and Lactococcus lactis expressing the S. agalactiae immunogenic proteins have been studied against streptococcosis disease in tilapia hosts [ 31 , 38 , 39 , 40 ]. Nevertheless, their relative percentage survival results still fluctuated, and some formulations also depended on oil adjuvants [ 27 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, oral vaccines based on live attenuated S. agalactiae , E. coli , Bacillus subtilis and Lactococcus lactis expressing the S. agalactiae immunogenic proteins have been studied against streptococcosis disease in tilapia hosts [ 31 , 38 , 39 , 40 ]. Nevertheless, their relative percentage survival results still fluctuated, and some formulations also depended on oil adjuvants [ 27 , 31 ]. Consequently, the development of fish oral vaccines based on encapsulation and entrapment strategies should receive more concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation